Trametinib response in heavily pretreated high-grade ovarian cancer: One step towards precision medicine - Serena Cappuccio; Maria Grazia Distefano; Viola Ghizzoni; Anna Fagotti; Giovanni Scambia (Elsevier, 2020)
Traditional treatment failure in recurrent ovarian cancer remains a challenge for clinicians. Tumor genetic testing is a promising tool which has been proved able to identify sensitivity profiles in patients affected by cancers. This may be helpful in choosing targeted systemic treatments, aiming to overcome histology boundaries and to avoid unnecessary toxicity. We describe the case of a patient affected by recurrent high-grade serous ovarian cancer responsive to MEK-inhibitors, who had undergone multiple lines of therapy. To our knowledge, this is the first reported case of recurrent high-grade ovarian cancer showing remarkable clinical, radiologic and biochemical response to trametinib. This report suggests that trametinib could be effective in high-grade serous ovarian cancer, although most of promising scientific data on this molecule have focused on low-grade ovarian cancer. Molecular profiling has gradually become part of care for patients affected by recurrent ovarian cancer, however further randomized studies are needed to prove its efficacy in everyday clinical practice.